Effectiveness of the Conceptual Understanding Procedures (CUPS) Learning Model on Students' Higher-Order Thinking Skills in Basic Chemical Law Material - Dea Pinangi; Mangara Sihaloho; Erga Kurniawati; Weny A Musa; Haris Munandar; Julhim S Tangio; Wiwin Rewini Kunusa (Jambura Journal of Educational Chemistry, 2025)
Students’ higher-order thinking skills in chemistry remain low due to the dominance of conventional teaching methods. This study aimed to investigate the effect of the CUPS (Conceptual Understanding Procedures) learning model on students’ higher-order thinking skills in the topic of basic laws of chemistry. Using a quasi-experimental design with a pretest-posttest control group, two classes of 28 students each from SMAN 1 Suwawa were selected as the experimental (CUPS-based learning) and control (conventional learning) groups. Data were analyzed using independent sample t-test. Results showed a greater improvement in the experimental class (pretest = 61, posttest = 79) compared to the control class (pretest = 39, posttest = 64). A significant difference was found between the groups (p = 0.001 < 0.05), leading to the rejection of the null hypothesis. These findings indicate that the CUPS learning model positively enhances students’ higher-order thinking skills, suggesting its potential for improving chemistry education